Sociodemographic and clinical aspects of quality of life related to oral health in adolescents - Peres, Karen Glazer; Cascaes, Andreia Morales; Leao, Anna Thereza Thome; Cortes, Maria Ilma de Souza; Vettore, Mario Vianna (Revista de Saúde Pública, 2013)
OBJECTIVE: To estimate the prevalence and to identify sociodemographic and oral health factors associated with the negative impact of oral health conditions on the quality of life in adolescents. METHODS: Data from 5,445 adolescents aged 15-19, who took part in the Brazilian Oral Health Survey (SBBrasil 2010) were analyzed, using a multistage sampling design. The outcome was quality of life related to oral health, which was assessed using the Oral Impacts on Daily Performance questionnaire and analyzed as a discrete variable. The independent variables were sex, skin color, schooling, household income, age, untreated dental caries, malocclusion.,gingival bleeding, dental calculus, and periodontal pocket. Poisson regression analysis was carried out and mean ratios (MR) with their respective 95% confidence intervals (95%CI) were presented. RESULTS: Of the total, 39.4% reported at least one negative impact on their quality of life. After adjustment, the mean negative impact was 1.52 (95%CI 1.16;2.00) times higher in females and 1.42 (95%CI 1.01;1.99), 2.66 (95%CI 1.40;5.07) and 3.32 (95%CI 1.68;6.56) higher in those with brown, yellow, and indigenous skin color, respectively, when compared to those with white skin. The lower the level of schooling, the greater the negative impact (MR 2.11, 95%CI 1.30;3.41), likewise for individuals with household income below R 500.00 (MR 1.84, 95%CI 1.06;3.17) compared with those with higher incomes. The greatest impact on quality of life was found among adolescents with four or more teeth with untreated dental caries (MR 1.53, 95%CI 1.12;2.10), one or more missing teeth (MR 1.44. 95%CI 1.16;1.80). those with dental pain (RM 3.62, 95%CI 2.93;4.46) and with severe (MR 1.52, 95%CI 1.04;2.23) and very severe malocclusion (MR 1.32, 95%CI 1.01;1.72). CONCLUSIONS: Brazilian adolescents reported a high negative impact of oral health on their quality of life. Inequalities in distribution should be taken into account when planning preventive, monitoring and treatment strategies for oral health problems in groups with the highest impact on their quality of life.